Nanotubes and Nanowires - Rao, C. N. Ram; Govindaraj,A (Royal Society of Chemistry, The Ingram Publisher Services [Distributor], 2011)
Annotation This volume provides a survey of the research areas of carbon nanotubes, inorganic nanotubes and nanowires including synthesis, characterisation, properties and applications. An extensive list of references are ideal for graduates needing an introduction to the field as well as professionals and researchers.
Keywords: Nanotubes.; Nanowires.; elektronické knihy; electronic books